"C" shaped dual polarized dielectric resonator antenna for the microwave imaging of breast tumor using beam‐forming algorithms. Issue 7 (16th April 2022) - Kaur, Gagandeep; Kaur, Amanpreet
Abstract: In this article, an ultra‐wideband (UWB) monostatic radar based microwave imaging (MWI) approach is proposed to detect the presence and localize the position of breast tumor in women (usually greater than 45 years of age). For this purpose, a "C" shaped elliptically polarized DRA (dielectric resonator antenna) with an impedance bandwidth of 7.3 GHz (i.e., 3.4–10.7 GHz) covering the UWB has been proposed as a sensor to record the backscattered S parameter signals from the breast tissues. This is done by rotating the proposed DRA in monostatic radar configuration around the breast phantom with an interval of 30° in elevation (0–180) and azimuthal planes (0–360), respectively. The recorded " S " parameter data is then processed using beam‐forming algorithms namely delay and sum (DAS), improved delay and sum (IDAS), delay multiply and sum (DMAS) to form 2D images of the breast tumor and locate its position (using MATLAB R 2013a). The design and simulation of the entire set up that includes the C shaped UWB DRA & Bio media (breast phantom) is done using CST MWS V'17. The fabrication of the proposed DRA is carried out using wet etching and water jet cutting process. The physical model of the Bio media is prepared using gelatin (skin), petroleum‐jelly (fat), and wheat‐flour (tumor). The validation of antenna radiation parameters is done using a VNA (vector network analyzer) model no. E5063A and good agreement between the simulated and measured results is observed. The proposed C shaped DRA is used in a monostatic radar based configuration to collect " S " parameters and the data is processed in a GPU to reconstruct a 2D image of the scanned breast phantom area. The size and detected location of tumor using beam‐forming is also close to the actual physical location of tumor with an error of 6.2% from the actual tumor location.